2019
DOI: 10.1016/j.mex.2019.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Community health assessment: Knowledge, attitude and practice of women regarding water-pipe smoking in Bandar Abbas

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Such awareness programs should be welltargeted to pregnant women from the lowest socio-economic households. To elaborate more, our previous work showed that women with lower socio-economic status had lower knowledge regarding health effects of water pipe and higher unfavorable attitude towards water pipe smoking (3). In case of cigarette smoking, it is shown that to achieve the same risk of growth restriction as non-smoking mothers, quitting must be adopted before conception (9, 10), although it is still efficient at earlier points during pregnancy (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such awareness programs should be welltargeted to pregnant women from the lowest socio-economic households. To elaborate more, our previous work showed that women with lower socio-economic status had lower knowledge regarding health effects of water pipe and higher unfavorable attitude towards water pipe smoking (3). In case of cigarette smoking, it is shown that to achieve the same risk of growth restriction as non-smoking mothers, quitting must be adopted before conception (9, 10), although it is still efficient at earlier points during pregnancy (18).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the well-established adverse effects of cigarette smoking on pregnancy outcomes (1), attention now has been shifted to other types of tobacco use, such as water-pipe smoking. The tradition of water pipe (also known as narghile, hookah, and shisha) dates back 400 years in Turkey, India, and Iran (2) and it is widely believed to be a less harmful form of tobacco consumption and a safer alternative to cigarette smoking (3). In the south of Iran, reports have shown that approximately 8.0-14.0% of preg nant women use water pipe regularly (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Encouragement to initiate prenatal healthcare services as soon as possible may assist pregnant women in making the decision to quit water pipe in pregnancy. Such awareness programs should pay special attention to pregnant women from disadvantaged socio-economic households, since our previous work showed that lower socio-economic status was strongly related to less knowledge and attitude about the adverse effects of water pipe smoking (3). In case of cigarette smoking, it has been shown that to achieve the same risk of growth restrictions as non-smoking mothers, quitting must be adopted before conception (9,10), although it is still efficient at earlier points during pregnancy (18).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the well-established adverse effects of cigarette smoking on pregnancy outcomes (1), attention now has been shifted to other types of tobacco use, such as water-pipe smoking. The tradition of water pipe (also known as narghile, hookah, and shisha) dates back 400 years in Turkey, India, and Iran (2), and in spite of deleterious health effects, it is widely believed to be a less harmful form of tobacco consumption, and a safer alternative to cigarette smoking (3). In the south of Iran, reports have shown that approximately 8.0-14.0% of preg nant women use water pipe regularly (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the well-established adverse effects of cigarette smoking on pregnancy outcomes [1], attention now has been shifted to other types of tobacco use, such as water-pipe smoking. The tradition of water pipe (also known as narghile, hookah, and shisha) dates back 400 years in Turkey, India, and Iran [2] and it is widely believed to be a less harmful form of tobacco consumption and a safer alternative to cigarette smoking [3]. In the south of Iran, reports have shown that approximately 8.0-14.0% of pregnant women use water pipe regularly [4,5].…”
Section: Introductionmentioning
confidence: 99%